Empowerment Strategy Of Fishery Products As Economic Resilience In The Coastal Marine - Dirgantara, Rudi (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
The local wisdom empowerment program is one way to increase the economic resilience of a community, not least in Tegal, Central Java. As a coastal area, this area has abundant potential for marine products, and can be used as the main livelihood in improving community welfare. However, there are many obstacles faced by the community, including knowledge, technology, experience, capital, and marine product management facilities. Therefore, this study was conducted to reveal the use of marine products as a solution to food security and the economy of the people of Tegal. To answer the purpose of this research, qualitative methods are used as a natural way to obtain actual information related to the phenomena being observed. The subjects of this research are the coastal communities of Tegal Regency who work as fishermen, totaling 150 people. Research data obtained through surveys, interviews, and discussions. In the results of the study obtained information, the majority of coastal marine communities in Tegal work as fishermen, so that their main livelihood is fishing. However, the community is aware of the lack of knowledge, capital, equipment and so on. So that it has not been able to maximize marine products, as an added value to the community's economic resilience.